Supramolecular Engineering of Nanoceria for Management and Amelioration of Age‐Related Macular Degeneration via the Two‐Level Blocking of Oxidative Stress and Inflammation - Mingyu Xu; Yifan Zhou; Yufeng Xu; An Shao; Haijie Han; Juan Ye (Advanced Science)
Abstract Age‐related macular degeneration (AMD), characterized by choroidal neovascularization (CNV), is the global leading cause of irreversible blindness. Current first‐line therapeutics, vascular endothelial growth factor (VEGF) antagonists, often yield incomplete and suboptimal vision improvement, necessitating the exploration of novel and efficacious therapeutic approaches. Herein, a supramolecular engineering strategy to construct moringin (MOR) loaded α‐cyclodextrin (α‐CD) coated nanoceria (M@CCNP) is constructed, where the hydroxy and newly formed carbonyl groups of α‐CD interact with the nanoceria surface via O─Ce conjunction and the isothiocyanate group of MOR inserts deeply into the α‐CD cavity via host–guest interaction. By exploiting the recycling reactive oxygen species (ROS) scavenging capability of nanoceria and the anti‐inflammation properties of MOR, the two‐level strike during AMD pathogenesis can be precisely blocked by M@CCNP. Remarkably, excellent therapeutic efficacy to CNV is observed in vivo, achieving over 80% reduction in neovascularization and over 60% reduction in leakage area. In summary, the supramolecular engineered nanoceria provides an efficient approach for amelioration of AMD by blocking the two‐level strike, and presents significant potential as an exceptional drug delivery platform, particularly for ROS‐related diseases.